2022
DOI: 10.3390/cancers14194678
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy-Chemoradiation for Borderline-Resectable Pancreatic Adenocarcinoma: A UK Tertiary Surgical Oncology Centre Series

Abstract: Background: Patients with borderline-resectable pancreatic ductal adenocarcinoma (BR-PDAC) have historically poor survival, even after curative pancreatic resection and adjuvant chemotherapy. Emerging evidence suggests that neoadjuvant chemoradiation (NCR) improves R0 resection rates in BR-PDAC patients. We evaluated the R0 resection rate, disease-free survival (DFS) and overall survival (OS) in our patients who underwent NCR for BR-PDAC at our institution. Methods: All patients who underwent NCR for BR-PDAC f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…According to the Authors, NAT is associated with a longer survival for patients with BRPC, but its broader efficacy in cases of resectable PDAC, and the optimal treatment strategy have yet to be established. In borderline resectable-locally advanced PDAC (BR/LAPC) patients NAT reportedly significantly increases the resection rate, the R0 resection rate, the node-negativity rate, and the median DFS and OS, 12 , 103 - 105 making it the treatment of choice for these patients.…”
Section: Role Of Nat In the Surgical Treatment Of Pdacmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Authors, NAT is associated with a longer survival for patients with BRPC, but its broader efficacy in cases of resectable PDAC, and the optimal treatment strategy have yet to be established. In borderline resectable-locally advanced PDAC (BR/LAPC) patients NAT reportedly significantly increases the resection rate, the R0 resection rate, the node-negativity rate, and the median DFS and OS, 12 , 103 - 105 making it the treatment of choice for these patients.…”
Section: Role Of Nat In the Surgical Treatment Of Pdacmentioning
confidence: 99%
“…Thanks to recently expanded neoadjuvant treatment options and increasing confidence with vascular resections (and arterial resection and reconstruction in particular), many patients previously deemed to have borderline resectable or locally advanced disease underwent successful pancreatic surgery, with or without vascular resection. 12 , 13 This review summarizes and analyzes recent advances in the surgical treatment of PDAC relating to the management of peripancreatic vessels during the resection procedure.…”
Section: Introductionmentioning
confidence: 99%
“…In borderline resectable PDACs, higher rates of R0 resections and longer disease-free and overall survival rates have been reported when FOLFIRINOX-based neoadjuvant treatments are used[ 17 ]. Recently, a prospective multicenter phase 2 trial demonstrated promising results when gemcitabine plus nab-paclitaxel chemotherapy were administered before surgery[ 18 ].…”
Section: Introductionmentioning
confidence: 99%